Do Reorganization Costs Matter for Efficiency? Evidence from a Bankruptcy Reform in Colombia - Giné, Xavier; Love, Inessa (World Bank, Washington, DC, 2012)
The authors study the effect of reorganization costs on the efficiency of bankruptcy laws. They develop a simple model that predicts that in a regime with high costs, the law fails to achieve the efficient outcome of liquidating unviable businesses and reorganizing viable ones. The authors test the model using the Colombian bankruptcy reform of 1999. Using data from 1,924 firms filing for bankruptcy between 1996 and 2003, they find that the pre-reform reorganization proceeding was so inefficient that it failed to separate economically viable firms from inefficient ones. In contrast, by substantially lowering reorganization costs, the reform improved the selection of viable firms into reorganization. In this sense, the new law increased the efficiency of the bankruptcy system in Colombia.